OsMFS1/OsHOP2 Complex Participates in Rice Male and Female Development - Lu, Jiayu; Wang, Chaolong; Wang, Haiyu; Zheng, Hai; Bai, Wenting; Lei, Dekun; Tian, Yunlu; Xiao, Yanjia; You, Shimin; Wang, Qiming; Yu, Xiaowen; Liu, Shijia; et al. (Frontiers in Plant Science, 2020)
Meiosis plays an essential role in production of gametes and genetic diversity of posterities. The normal double-strand break (DSB) repair is vital to homologous recombination (HR) and occurrence of DNA fragment exchange, but the underlying molecular mechanism remain elusive. Here, we characterized a completely sterile Osmfs1 (male and female sterility 1) mutant that their pollens and embryo sacs were both aborted at the reproductive stage due to severe chromosome defection. Map-based cloning revealed that the OsMFS1 encodes a meiotic coiled-coil protein, and it is responsible for DSB repairing that acted as an important cofactor to stimulate the single strand invasion. Expression pattern analyses showed the OsMFS1 was preferentially expressed in meiosis stage. Subcellular localization analysis of OsMFS1 revealed its association with the nucleus exclusively. In addition, a yeast two-hybrid (Y2H) and pull-down assay showed that OsMFS1 could physically interact with OsHOP2 protein to form a stable complex to ensure faithful homologous recombination. Taken together, our results indicated that OsMFS1 is indispensable to the normal development of anther and embryo sac in rice.